RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS BAUJI TERHADAP PERLAKUAN DOSIS PUPUK KANDANG SAPI DAN PUPUK NPK - Edy Soenyoto (Jurnal Ilmiah Hijau Cendekia, 2016)
These trials were conducted in Puhjarak Village, District Plemahan, Kediri at an altitude of ± 138 M above sea level. With this type of Gromosol soil, with a pH of 5.8. The study was conducted on 14 September 2015 until November 5, 2015. The experimental design used was a randomized block design (RAK) factorial. As the first factor is the dosage of cow manure (K) consists of four levels, namely Ko: no fertilizer treatment, K1: cow manure 5 tons / ha, K2: cow manure 7.5 tonnes / ha, and K2: Manure cattle 10 tons / ha. A second treatment factor NPK (N) consists of three levels: N1: NPK fertilizer with a dose of 150 kg / ha, N2: NPK fertilizer with a dose of 200 kg / ha, N3: NPK fertilizer with a dose of 250 kg / ha. This study aims to determine the response of growth and yield of onion (Allium ascalonicum L) varieties Bauji against sapidan dosage of NPK fertilizer manure. Based on the results of the study "Response Growth and Production of onion (Allium ascalonicum L.) varieties Bauji Against Cattle Manure Treatment Dosage And NPK" it can be concluded that: a very real interactions occur between dosage of cow manure and NPK fertilizer to variable plant height age 28 hst and real interaction on plant height variable age 42 HST and the number of leaf age 42 HST. Dosage of cow manure very significant effect on the variable-wet weight of tuber per plot and the real impact on variable dry weight of tuber per plot. The highest production was generated in the cowshed dose treatment of 7.5 tonnes / ha in the amount of 2.34 kg of dried tubers perpetak (11,700 kg / ha). Dosage of NPK fertilizer very significant effect on the variable number of tillers age 28 hst and significantly affect a variable number of tillers age 42 HST